Rancang Bangun Alat Hitung Indeks Massa Tubuh Berbasis Arduino - Erliwati, Erliwati (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
This study aims to design Arduino-based scales for weight, height, body mass index. Height and weight measuring device is a measuring tool that functions to measure the height and weight of a person's body. To measure height and weight in general, it is still done separately (separately) in this case the measurements of height and weight are carried out using different tools. By increasing the pace of technological advances, especially in the health sector, according to the author's observations, the height and weight measuring devices are still manual, it's time to increase their function, in this case, it is necessary to increase the function of the tool, especially those related to the field of electronics. The results of measuring weight using CAMRY brand scales with Karya Nesa scales, the average error rate is 0.037 (still within the tolerance threshold), while the results of measuring height are in accordance with the actual. From the results of the Body Mass Index (BMI) analysis with the results of the Body Mass Index (BMI) measurement by Nesa, it is correct and valid (valid). The error rate of weight or scales is relatively small, the accuracy of the scales is very good. The error rate is declared large, if the error is above 5% or greater than 0.05. Based on the results obtained, it is suggested that the scales need to be made precise (not rocking), this can be harmful to the patient and needs to be developed by adding sounds such as: weight, height and BMI results